Unlocking the Metaverse: Revolutionizing Resource Learning for Future Students - Darazha , Seitova; Glyussya, Malik (International Journal of Educational Technology and Artificial Intelligence, 2023)
Recently, the metaverse has emerged as a global focal point, drawing extensive attention thanks to rapid technological advancements. The forthcoming metaverse promises amplified direct physical interactions, diminishing the significance of traditional constructs such as race, gender, and physical disabilities, ultimately offering profound societal advantages. This study is a qualitative descriptive literature review to show how metaverse in the live Nonetheless, the metaverse’s development remains nascent, brimming with untapped potential. Despite proactive industry preparations and substantial investments, there’s a pressing need for expanded scholarly discourse on the metaverse to provide the scientific guidance necessary for its maturation. Metaverse-based learning has been presented as a blockchain-driven prototype, emphasizing its infrastructure, interaction features, and ecosystem elements. The metaverse aims to enrich university students’ and faculty’s campus life, aligning with the principles of accessibility, diversity, equality, and humanity. The study findings are developing an ecosystem for the metaverse, a journey through the evolution of the metaverse, and conducting a virtual campus.